1943
DOI: 10.1002/jez.1400930204
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the California sea‐mussel (Mytilus californianus). II. Nutrition, metabolism, growth and calcium deposition

Abstract: FOUR FIGURESI n a recent paper on the influence of temperature, food supply, sex and age on the rate of growth of this species, it was shown that on the coast of Southern California the mu+ sel under favorable conditions may reach a length of 80 to 86 mm. at the age of 1 year, 120 mm. when 2 years old and approximately 145 mm. at the end of the third year (Coe and Fox, '42). The habitat, food, digestion and salinity require- It now remains to consider some of the substances of which the body and shell of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

1945
1945
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…[10]), food availability [11] and predation pressure [12,13], some of which can interact, either counteracting the effects of changing seawater saturation state [11] or exacerbating them [3]. All of these factors probably contribute to how a species modulates calcification internally (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[10]), food availability [11] and predation pressure [12,13], some of which can interact, either counteracting the effects of changing seawater saturation state [11] or exacerbating them [3]. All of these factors probably contribute to how a species modulates calcification internally (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Seed, 1968) and water motion (i.e. velocity, wave impact, turbulence) (Aguirre et al, 2006; Fox and Plasticity of quagga mussel morphology Coe, 1943;Selin and Vekhova, 2003;Steffani and Branch, 2003) have been thought to affect shell morphology and growth of molluscs (e.g. Brachidontes sp., L. obtusata, Mytilus edulis, M.…”
Section: Introductionmentioning
confidence: 99%
“…However, investigation of food availability in natural seawater has shown that phytoplankton cells are seldom present MATERIALS AND METHODS in sufficient numbers to contribute significantly to the mussels' diet. Authors such as Fox and Coe (1943), Choromytilus meridionalis (Kr.) (45 mm shell length) Jerrgensen (1955) and Widdows et al (1979) have and seawater were sampled at Bailey's Cottage, False shown that particulate organic matter is the major food Bay, South Africa (34" 06's 18" 28'E).…”
Section: Introductionmentioning
confidence: 99%